Stereo vision system for a bin picking adept robot - Hema, Chengalvarayan Radhakrishnamurthy; Paulraj, Murugesapandian; Ramachandran, Nagarajan; Sazali, Yaacob (Universiti Malaya, 2009)
Link to publisher's homepage at http://ejum.fsktm.um.edu.my